2016
DOI: 10.1021/acs.cgd.5b01705
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Characterization of Bridged Steroidal Molecular Rotors: Effect of the Rotator Fluorination on Their Crystallization

Abstract: We describe the synthesis and crystallization of two macrocyclic steroidal compounds labeled (Z)-1F 2 and (E)-1F 2, envisioned to work as molecular rotors with 1,4-diethynyl-2,3-difluorophenylene rotators. The introduction of the fluorine atoms rendered different crystal arrays that were fully characterized by X-ray diffraction, solid state 13C NMR, and calorimetric experiments. In both isomers, the central molecular fragments point the o-fluorine atoms toward their cavity, highlighting the preferred orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…More recently, structural analysis of macrocyclic molecular rotors based on oxosteroid stators revealed that 1,4-diethynylphenylene rotators are close to linearity and comparatively distant from the bridging chain. However, the proximity of the bridging chain to neighboring rotators could restrict the internal rotation in the E isomers. , In this sense, the steroidal 12-oxosapogenins, spirostanic members of the steroidal sapogenins (SS), offer the possibility to introduce an alkyne axle at the C-12 position in order to build molecular rotors containing more shielded rotators with conformationally restricted stators with the aim to compare their dynamics and solid state structure with the corresponding bridged analogues. Hecogenin ( 1 ) is a steroidal sapogenin obtained from the family Agavaceae, which is used in the treatment of scabies, tumors, pain, inflammatory disorders, as a gastroprotective agent, and also for the synthesis of steroidal hormones.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, structural analysis of macrocyclic molecular rotors based on oxosteroid stators revealed that 1,4-diethynylphenylene rotators are close to linearity and comparatively distant from the bridging chain. However, the proximity of the bridging chain to neighboring rotators could restrict the internal rotation in the E isomers. , In this sense, the steroidal 12-oxosapogenins, spirostanic members of the steroidal sapogenins (SS), offer the possibility to introduce an alkyne axle at the C-12 position in order to build molecular rotors containing more shielded rotators with conformationally restricted stators with the aim to compare their dynamics and solid state structure with the corresponding bridged analogues. Hecogenin ( 1 ) is a steroidal sapogenin obtained from the family Agavaceae, which is used in the treatment of scabies, tumors, pain, inflammatory disorders, as a gastroprotective agent, and also for the synthesis of steroidal hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies directly target molecular gyroscopes and others less so, although there remains an obvious relevance. Thus, most of the groups’ work involving molecular rotors has been covered but with a few exclusions: (1) rotors that feature large biomolecules such as steroids as stators are not treated, as these have generally been prepared with goals other than molecular devices in mind; (2) rotors that are restricted to crankshaft type motions or are comprised of multiple nonparallel rotators , are likewise not treated.…”
Section: Systems From the Garcia-garibay Groupmentioning
confidence: 99%
“…Typically, stators are bulky molecular fragments covalently or supramolecularly linked to an alkynyl bridged phenylene (∼5 Å), diaza- or bicyclo[2.2.2]­octane (∼6 Å) and trypticene (∼11 Å) rotator. Depending on the rotator size and the organization in the crystal structure, these amphidynamic systems display a wide range of rotational frequencies (10 –6 to 10 –12 s –1 ), even at room temperature. During the past decade, our group has focused on the design and development of molecular rotors based on steroidal stators with acyclic, macrocyclic, and hybrid scaffolds (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the possibility to adopt different conformations (syn- and anti- modes) results in rotator–stator interdigitation, as well as in the formation of different conformational polymorphs. For this reason, we explored macrocyclic systems in order to control the conformational flexibility and restrict the plausible crystalline arrays. Derived from this research, we have found that the stereochemistry of the bridging fragment plays a crucial role in minimizing the conformational degrees of freedom of the steroidal stator; nevertheless, even in these systems rotator–stator interdigitation is present. In recent studies, a family of steroid-flanked derivatives of p -nitroaniline was explored; these molecules exhibit interdigitated organization with promising characteristics for nonlinear optics, organic electronic materials, and molecular recognition .…”
Section: Introductionmentioning
confidence: 99%